Chapter Public History, identità professionale e riflessività degli educatori e degli insegnanti - CAUSARANO, PIETRO (Public History of Education. Teorie, esperienze, strumenti, 2022)
The great transformations that have affected the function and the teaching role in recent decades, have undermined the mechanisms of traditional construction of professional identity. The Public History can be useful in reconstructing the forms and contents of teaching professionalism in a reflective perspective.